The Role of the Government’s Self- Depth in Bearing Financial Pressures in Iraq for the Period (2006-2022) - Abdulkareem Abdulhussein, Shatha; Mohammed Ali Abdullatif, Emad (Journal of Economics and Administrative Sciences, 2024)
This study aimed at analyzing the government’s self-financing depth in withstanding financial pressures in Iraq during the period (2006-2022). The study assumed that increasing government’s financial capacity was having a positive impact on facing financial pressures of public expenditure burdens and economic non-stability in Iraq. The study relied on the inductive and data analysis method to verify the hypothesis of the study and access to results. With reference to the use of the ratio of oil revenues to GDP as deputy for self- financing depth due to the Iraqi government’s heavy reliance on oil revenues to finance the general budget. It also used the following indicators as deputy financial pressure: the ratio of public expenditure, consumption, investment, and public debt to gross domestic product, tax effort index, monetary stability coefficient index and, exchange rate discipline index. The study found that the financial capacity of the Iraqi government relied heavily on volatile self-financing depending on the volatility of oil revenues in financing current expenditures, which reduced the financial capacity to stand financial pressure. It’s reflected in the government’s high financial burden and the existence of economic non-stability (inflation pressure, external debt pressure, foreign currency exchange pressure) in Iraq. Paper type: Research paper.